Revue des recherches universitaires sur Toastmasters International - Kalińska, Sylwia (2022)
Since 1905, Toastmasters International has been the world’s best-known organization for the practice of voluntaryspeaking. At Toastmasters, members learn by studying their manual, doing hands-on exercises, and helping eachother. This manual offers ten projects: each of them aims to develop an aspect of oral communication followinga well-defined progression. Since there is little academic research regarding the use of the Toastmasters method,we want to present in this article a review of the existing research. The studies described below constitute themost important academic literature as far as Toastmasters International is concerned. The authors’ research onToastmasters encompasses three main themes: (1) Toastmasters International as an educational program, (2) socialease among members, or (3) public speaking anxiety. We will present them in chronological order.
Keywords: Toastmasters International; public speaking; anxiety; academic research